Online practicum preparation for enhancing preservice teachers' reflection depths: a quasi-experimental approach - Wang, Ye; Ko, James; Lam, Elaine (Frontiers in Education, 2023)
Building preservice teachers' capacities with in-depth reflections on their acquired knowledge and practicum practice has become indispensable in teacher education programs' current field experience requirements. Lengthy training programs with blended learning have successfully promoted reflections in preservice teachers. However, it is wanting whether preservice teachers could benefit from a short self-access online training program (SSOTP) in promoting their reflection depths, especially when facing challenging situations like COVID-19. Results suggested that establishing an SSOTP with systematic stimulations could enhance preservice teachers' reflection depths and help them achieve quality teaching during the teacher preparation stage. Using a teaching and assessing reflective learning model, this study showed the effectiveness of an SSOTP in stimulating reflection depth among Chinese preservice teachers during practicum preparation in a quasi-experimental research approach. The training sequence and different topics also significantly affected preservice teachers in generating reflections. While preservice teachers generated many reflective statements, their reflection depths were relatively shallow. This study provided evidence to enhance different levels of reflection depth in future SSOTP.